Hubungan Konsep Diri dan Kecerdasan Emosi dengan Kemampuan Penyesuaian Diri pada Remaja - Mutamminah, Mutamminah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. The research aims to know the relationship between self concept and emotion intelligent with the capable self appropriate to adolescent. The subject of research is 107 the students of Muhammadiyah senior high school 4 Sidayu Gresik. The data analysis used regression got F the large 12,756 with p = 0,000 (p< 0,01) its mean any significant relationship between self concept and emotion intelligent with the capable self appropriate to adolescent. The analysis of variable data is self concept with the capable self appropriate to adolescent got the result with the large t = 3,404 with p = 0,001 (p < 0,05) it’s mean any significant relationship between self concept with the capable self appropriate to adolescent. The variable data analysis emotion intelligent with the capable self appropriate to adolescent the results with the large t = 2,435 with p = 0,017 (p < 0,05) it’s mean any significant relationship between emotion intelligent with the capable self appropriate to adolescent. The percentage contribute self concept affective and emotion intelligent with the capable self appropriate to adolescent a lot of 19,7 %.Keywords: self concept, emotion intelligent and the capable self appropriate to adolescent.